Mitigating Life Challenges to Subjective Well-being through Civic Engagement: Insights from a Global Perspective - Fengyu Wu; Jeffrey B. Nugent (Global Labor Organization (GLO), 2024)
This paper investigates the role of civic engagement, an important form of social capital from the supply side, in buffering the adverse effects of challenging life circumstances in three key domains-employment, marriage, and health-on individual subjective well-being, specifically in terms of overall life evaluations. Our findings reveal that the negative association between divorce, separation, or widowhood and overall life evaluations can be mitigated through active associational memberships (of both the Putnam and Olson types), and three forms of civic engagement in broader network structures (i.e., donating money, volunteering, and helping strangers). In situations of poor health, however, only Olson-type memberships, donating money, volunteering, and helping strangers are found to mitigate the negative association with overall life evaluations. Furthermore, the negative association between unemployment and overall life evaluations is alleviated only by Putnam-type memberships. We also explore heterogeneity in the extent of such mitigation across individual characteristics (e.g., gender and age) and country-level factors (e.g., level of development and region). Finally, we find that the most commonly studied measure of social capital, namely, social trust, does not serve as a significant mediator in any of the relationships examined. Our analysis utilizes data from waves 3, 5, 6, and 7 of the World Values Survey and the Gallup World Poll conducted between 2009 and 2021.
Keywords: I31; Z13; A13; J64; J12; I10; 330; Subjective Well-being; Life Satisfaction; Social Capital; Civic Engagement; Challenging Life Conditions